Regional Budget Management Strategy to Improve Local Government Performance - Karlina Napu; Feri Hulukati (Eastasouth Institute, 2026)
Regional budget management serves as a strategic instrument in realizing effective and accountable local government performance. This study aims to analyze various regional budget management strategies and their impact on improving local government performance through a qualitative literature review approach. The method used is a systematic literature review by analyzing 25 reputable journal articles published between 2023 and 2025. The analysis was conducted through theme identification, synthesis of findings, and critical evaluation of budget management strategies, including performance-based budgeting, transparency and accountability, efficiency and effectiveness, as well as the digitalization of regional financial systems. The results show that the performance-based budgeting strategy contributes significantly to improving local government performance, with an average effectiveness rate of 82.5%. Transparency and accountability in financial management positively influence public trust and the financial performance of local governments. The implementation of integrated regional financial information systems increases budget management efficiency by up to 35%. However, challenges in implementation include resistance to change, limited human resource capacity, and lack of coordination among regional work units (Regional Apparatus Organizations or OPD). This study recommends the adoption of a holistic approach that integrates technical, managerial, and information technology aspects in regional budget management, as well as the strengthening of personnel capacity through continuous training to optimize local government performance.